2016
DOI: 10.1080/21622965.2016.1210011
|View full text |Cite
|
Sign up to set email alerts
|

SCAT3 assessment of non-head injured and head injured athletes competing in a large international youth soccer tournament

Abstract: To our knowledge, no study has evaluated Sideline Concussion Assessment Tool -3rd Edition (SCAT3) scores during competition in athletes who have not had a head injury. The purpose of our pilot study was to compare SCAT3 scores in non-injured (NI), injured (but not head injured) (I), and head injured (HI) youth soccer players during competition and to establish preliminary baseline data for non-head injured athletes in a competitive setting. The HI group demonstrated significantly more symptoms (M = 9.7, SE = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
3
8
0
Order By: Relevance
“…It also builds upon existing validity literature for SCAT3 in teenagers and young adults, further supporting the notion that it can distinguish among concussed and control groups. 13,14 Concordant with the limited SCAT3 literature, our results indicate that the SAC is not useful in the acute differentiation of those with and without concussion (although it may have an important role in monitoring recovery in the subacute period), and further investigation is required. 13,21 Given the pending development of the SCAT5 and ChildSCAT5, the current study provides evidence in support of the ability of the SCAT3 and ChildSCAT3 to differentiate between children with and without a concussion in an acute ED setting.…”
Section: Figuresupporting
confidence: 68%
See 1 more Smart Citation
“…It also builds upon existing validity literature for SCAT3 in teenagers and young adults, further supporting the notion that it can distinguish among concussed and control groups. 13,14 Concordant with the limited SCAT3 literature, our results indicate that the SAC is not useful in the acute differentiation of those with and without concussion (although it may have an important role in monitoring recovery in the subacute period), and further investigation is required. 13,21 Given the pending development of the SCAT5 and ChildSCAT5, the current study provides evidence in support of the ability of the SCAT3 and ChildSCAT3 to differentiate between children with and without a concussion in an acute ED setting.…”
Section: Figuresupporting
confidence: 68%
“…12 Recently, the ability of SCAT3 to discriminate between high-school athletes with and without concussion has been investigated. 13,14 To our knowledge, only 2 studies have considered the psychometric properties of ChildSCAT3, although neither considered concurrent validity. 15,16 The aim of the current study was to determine if SCAT3 and ChildSCAT3 can differentiate children with and without concussion during acute presentation to the ED.…”
mentioning
confidence: 99%
“…The average number of SCAT3 symptoms endorsed has been estimated between 1.75 and 3.2 for the general population. [15][16][17] By comparison, the number of these symptoms endorsed by youth athletes who sustained HIs was 9.7. 16 Consistent with these studies, our data revealed a higher number of postconcussive symptoms endorsed by cyclists who reported HIs versus those who did not.…”
Section: Discussionmentioning
confidence: 98%
“…[15][16][17] By comparison, the number of these symptoms endorsed by youth athletes who sustained HIs was 9.7. 16 Consistent with these studies, our data revealed a higher number of postconcussive symptoms endorsed by cyclists who reported HIs versus those who did not. Cyclists in the TC group indicated, on average, 1 or no postconcussive symptoms, whereas cyclists with HI indicated an average of 5.75 symptoms; the SCAT is the most wellestablished screening tool across sports, and the SCAT symptoms checklist is likely a valuable screening tool in this population.…”
Section: Discussionmentioning
confidence: 98%
“…Another study was conducted by Gorman et al, for assessing SCAT3 in non-head-injured and head-injured athletes competing in an international youth football tournament (18). They studied SCAT3 components in three groups of players including non-injured (NI), injured (but not head injured) (I), and head injured (HI) players.…”
Section: Discussionmentioning
confidence: 99%